"Перестройка" v. Реформи. Яка модель дає шанс е-уряду? - Яковлев, Денис (Видавництво Львівської політехніки, 2015)
The article investigates the type of reforms that could implement the egovernment model. It has been determined that the defeat of the Soviet project "Perestroyka" led to the dominance of a liberal model of reforms in the Ukrainian political discourse. But it has never been implemented. It has been noted that in current conditions the liberal model resembles the surgery, while Ukraine needs therapy. The reforms, which will allow to create e-government, should be based on reflection and consent of participants – from political actors to the civil society.
Keywords: е-уряд; е-демократія; перебудова; модернізація; реформи; рефлексія; політичний вибір